Fusion of glioma-associated mesenchymal stem/stromal cells with glioma cells promotes macrophage recruitment and M2 polarization via m6A modification of CSF1 - Zhen Liu; Sujie Gu; Zesheng Peng; Yihao Wang; Hui Li; Xiaoqing Zeng; Haofei Wang; Peng Lv; Yuyi Wu; Yan Zhou; Yanbin Zhang; Xiaobing Jiang; et al. (Cell Death and Disease)
Abstract Malignant glioma is the most common primary malignant tumor of the brain in adults, with glioblastoma (GBM) being the most aggressive subtype. Mesenchymal stem/stromal cells (MSCs) have been shown to fuse with tumor cells in various cancers including glioma, thereby regulating tumor progression. However, there has been no systematic research on the fusion of glioma-associated MSCs (GA-MSCs) with glioma cells. Here, it is shown that GA-MSCs are able to spontaneously fuse with glioma cells both in vitro and in vivo. The hybrid cells display significantly lower levels of N6-methyladenosine (m6A) modification and can modulate the glioma microenvironment by attracting and inducing M2-like polarization of macrophages. Mechanistically, the demethylase fat mass and obesity-associated protein (FTO) mediates demethylation in hybrids and promotes macrophage colony-stimulating factor (CSF1) secretion by increasing its RNA stability in an m6A-YTH domain family 2 (YTHDF2)-dependent manner. Our study reveals a novel crosstalk mechanism between glioma cells, GA-MSCs, and macrophages in glioma microenvironment, offering potential new approaches for glioma therapy.